Strategi Mitigasi Risiko Supply Chain Pengadaan Bahan Baku Kayu Pada Industri Furnitur - Ma'rifah, Julia Dewi; Amarta, Zain (Benefit: Jurnal Manajemen dan Bisnis, 2023)
The furniture industry is one of the potential industries in Indonesia with an export value of up to USD 3.5 billion in 2022. The utilization of wood raw materials in the furniture industry is one of the main aspects of furniture manufacturing. Various risks in the supply chain process for procuring wood raw materials can cause losses and obstacles that affect the productivity of the furniture industry. This study aims to develop and select an effective risk mitigation strategy in the process of procuring wood raw materials in one of the furniture industries in Semarang, Central Java, namely PT ABC. House of Risk (HOR) is used in this research method by identifying risk events, risk agents and determining the choice of an effective risk mitigation strategy according to the Effectiveness to Difficulty (ETD) value. The results showed that there were a total of 18 risk events and 21 risk agents in PT ABC's wood raw material procurement process. The first phase HOR produces 5 priority risk agents including A11, A14, A2, A15, and A9 with each Aggregate Risk Potential (ARP) value of 936, 540, 420, 396 and 324. The second phase HOR produces 5 preventive actions with the highest ETD values are PA2, PA33, PA6, PA7, PA4 with ETD of 3096, 2241, 1260, 1260 and 1215.